HISTOGRAM E QUALIZATION SMOOTHING FOR DETERMINING THRESHOLD ACCURACY ON ANCIENT DOCUMENT IMAGE BINARIZATION - Dwipayana, Mahendar; Arnia, Fitri; Musliyana, Zuhar (Ubudiyah Indonesia University, 2016)
Ancient documents are inheritance that must be preserved. Thedocuments contain historical, scientific, social, religious information, etc.Converting ancient documents into digital image formats is one of ways topreserve the inheritance and can be stored into a computer. However,images of ancientdocuments have many blemishes caused by age,moisture, flood, etc. Therefore, special techniques are needed for thoseimages to be restored and can improve the legibility of the ancientdocuments’ images. In this study, the image restoration process usesseparation of background and foreground/text on histogram equalizationsuch as research conducted by Fitri Arnia in 2008. Through histogramequalizationimages can be seen the distribution of pixels from the intensityof black color